Прогностичне значення функціонального стану дендритних клітин у безплідних жінок із зовнішнім генітальним ендометріозом = The importance of prognostic functional condition of dendritic cells in barren women with external genital endometriosis - O. M. Stepanovichus (Kazimierz Wielki University, 2015)
Stepanovichus O. M. Прогностичне значення функціонального стану дендритних клітин у безплідних жінок із зовнішнім генітальним ендометріозом = The importance of prognostic functional condition of dendritic cells in barren women with external genital endometriosis. Journal of Education, Health and Sport. 2015;5(11):197-202. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.33763 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A197-202 https://pbn.nauka.gov.pl/works/668907 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 10.11.2015.   УДК: 618.177-06:618.145-007.415:611.018.83]-036   ПРОГНОСТИЧНЕ ЗНАЧЕННЯ ФУНКЦІОНАЛЬНОГО СТАНУ ДЕНДРИТНИХ КЛІТИН У БЕЗПЛІДНИХ ЖІНОК ІЗ ЗОВНІШНІМ ГЕНІТАЛЬНИМ ЕНДОМЕТРІОЗОМ The importance of prognostic functional condition of dendritic cells in barren women with external genital endometriosis   О. М. Степановічус O. M. Stepanovichus   Одеський національний медичний університет Одеса, Україна Odessa  National Medical University Odessa, Ukraine   Resume The observation results of 120 barren women with  external genital endometriosis  are given in the article. The age of examined patients  is from 21 to 35 years. Decrease of mature dendritic cells activity after immune histochemical  observation up (5,2±0,5 cl./мм2 СD23 in the functional layer and up to 6,0±0,5 cl./мм2 in the basal layer) and increase of immature dendritic cells activity in basal layer (CD1a to 34,2±1,2 cl./мм2) were revealed. The differences between examples on these indicators were reliable. All that is mentioned above is the indication of functional suppression of local immunity and can be a factor which decreases reproductive function that requires immediate diagnostics with immunocorrection. Key words׃ barren women, endometrios, dendritic cells.   Резюме В статті наведені результати спостереження  120  безплідних хворих із зовнішнім генітальним ендометріозом. Вік обстежених хворих склав від 21 до 35 років. При імуногістохімічному дослідженні було виявлено зниження активності зрілих дендритних клітин (до 5,2±0,5 кл./мм2 СD23 у функціональному шарі та до 6,0±0,5 кл./мм2 у базальному шарі) і підвищення активності незрілих дендритних клітин у базальному шарі (CD1a до 34,2±1,2 кл./мм2). Відмінності між зразками по названих показниках були достовірними (р<0,05). Все вишезазначене є свідоцтвом функціональної супресії місцевого имунітету і може являться фактором, який знижує репродуктивну функцію, що в свою чергу потребує негайної діагностики з послідуючим проведенням імунокорекції. Ключові слова: безплідні жінки, ендометріоз, дендритні клітини.